Heterogeneity in Income Tax Capitalization: Evidence from the Swiss Housing Market - Mario Morger (Swiss Journal of Economics and Statistics, 2017)
There is evidence that taxes capitalize into housing prices, but great uncertainty about the magnitude of income tax capitalization. One explanation why empirical evidence is unclear may stem from the fact that capitalization is something personal, depending on income, mobility, and on the individual tax burden of the bidding households. Therefore, income tax capitalization may theoretically differ substantially between different housing price segments. Results obtained from the analysis of a large Swiss dataset suggest that capitalization is lower for apartments for rent compared to apartments for sale. Capitalization is insignificant or less than 100% for all rental segments. Concerning apartments for sale, capitalization is well above 100% for the low and top price segments.
Keywords: H22; H73; R21; R38; 330; housing prices; income tax capitalization; segregation